Upaya Non Penal Terhadap Tindak Pidana Pencurian Bernilai Ringan di Mini Market - Gusti Ayu Euanggelin Marsha Wangania; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2022)
Crime is a problem that arises from many factors that support it where there is a violation of the rules that should be obeyed by the community itself, and it is undeniable that the crime comes from the community. Some cases of criminal acts are also caused by economic problems, theft is a common crime, where someone robs another person of wealth or objects. The purpose of this study is to find out the settlement of the crime of theft of light value in mini markets with non-penal alternatives, and the obstacles to solving the crime of theft of light value in mini markets with non-penal alternatives. The type of research used in this research is empirical legal research, the sources of legal material are obtained by conducting interviews and literature studies. The results of the study indicate that the settlement of the crime of minor theft in the mini market is by non-penal efforts, which can be carried out with preventive efforts, namely efforts that can be made before the occurrence of a crime by dealing with the factors driving the occurrence of a crime. In terms of solving the problem of minor crimes, there is one solution that is considered to be able to humanize humans, namely Restorative Justice. There are 2 (two) obstacles in resolving cases of theft of light value in mini markets with non-penal alternatives, namely internal and external factors.